Meningkatkan Motivasi Belajar Bagi Mahasiswa Kurang Berprestasi Melalui Program Mentoring - Lisa Ratriana Chairiyati (Humaniora, 2011)
This research is meant to study on how to increase motivation to study for students with low GPA through mentoring program at a private university in West Jakarta. The research design is descriptive with a sample of 70 active students. Data is obtained through total sampling method using questionnaires. This research uses instrument where processed data is constructed using likert scale and questionnaire result is shown in a score interpretation table. Data analysis results obtained using descriptive statistics show that scoring on mentoring program subject facility (65,14%), subject scoring on mentoring program, subject scoring on mentor performance (68,57%), shows that interpretation is in the range of strong to very strong. This shows that the mentoring program should be used as an alternative to motivate students with low GPA to study harder, therefore when they retake a subject where they failed before, they would be ready (70,86%)